Radical writers and the media revolution in the late Enlightenment - Streb, Christoph (Oxford University studies in the Enlightenment, 2024)
"This book offers a reassessment of radical writing in the late Enlightenment by examining the construction of a provocative authorial posture. It focuses on French and British writers who confronted the authorities as self-proclaimed outsiders, presented their authentic personalities to their readers, and boasted of their own political importance. This posture, and focus of the volume, was possible against the backdrop of an eighteenth-century media revolution that gave print a new presence in many people's daily lives. To stage protests, create scandals, and encourage political mobilisation, radical writers interacted with a growing and ever-curious audience consuming a variety of printed goods. Radical writing and the media revolution in the late Enlightenment features in-depth case studies of writers such as John Horne Tooke and Olympe de Gouges, among others. It also provides a systematic analysis of typical rhetorical gestures and paratextual forms that were frequently used to create a provocative posture. Finally, this study reconstructs contemporary anxieties about popular writers that have been largely overlooked by scholarship. Indeed, many proponents of the Enlightenment worried that emotions and entertainment were taking over public debate. Rather than siding for or against radical writing and the media revolution, this book uses these critical reactions to re-emphasise the ambivalence of popular politics in the late Enlightenment."-- Publisher's website
Literaturverzeichnis: Seite 255-296
Dissertation eingereicht unter dem Titel: Light or Fire? Publicists and the Mediatisation of Political Communication, 1760-1800
Keywords: Hochschulschrift; Geschichte 1750-1800; Politische Kommunikation; Politischer Stil; Politisches Engagement; Politisches Handeln; Schriftsteller; Großbritannien; Frankreich; Aufklärung